Readership Assessment of Missouri’s Discover&Enlighten: Implications for Publications and Teaching Programs - Sharon Wood-Turley; Mark Tucker (Journal of Applied Communications, 2003)
Readership analyses are among the most common types of evaluation research in agricultural communications today. The research reported here was undertaken to measure the effectiveness of Discover&Enlighten, a monthly newsletter published by the University of Missouri’s College of Agriculture, Food and Natural Resources. This study employed mail survey methods. A total of 335 reader names were randomly selected from the 2,700-member mailing list for inclusion in the sample. A structured questionnaire developed by the researchers assessed readers’ perceptions of the newsletter, their interest in various topics, and selected demographic characteristics. Descriptive and multivariate statistics are reported based on 150 completed questionnaires, or a total response rate of 45 percent. Findings indicate that respondents desire a mix of stories ranging from natural resources to life sciences to production agriculture. Findings also indicate generally positive perceptions toward the newsletter and delivery methods. Nearly 90 percent of the respondents indicated that Discover&Enlighten is a truthful source of information. Fewer than one fourth indicated a preference for receiving the newsletter electronically rather than in print form. The theoretical model developed to predict reader preferences for receiving the newsletter was shown to be only slightly successful.